Thermal, structural and optical properties of new TeO2-Sb2O3-GeO2 ternary glasses - Pereira, C. (2016)
In this work the novel glass system TeO2-Sb2O3-GeO2 was investigated and promising glass compositions were selected for further specific studies. Glass samples in the (80-0.8x)TeO2-(20-0.2x)Sb2O3-xGeO(2) molar composition were prepared by the melt-quenching method with a glass-forming domain from x = 10 to x = 90. Samples were investigated by XRD, DSC, FTIR, Raman spectroscopy and UV-visible absorption. The XRD and DSC results bring informations about the non-crystalline state and thermal properties of these materials. It has been observed that higher GeO2 contents lead to higher glass transition temperatures and thermal stabilities against crystallization. FTIR and Raman spectroscopies suggest a progressive incorporation of GeO2 in the covalent network of TeO2 with conversion of structural units TeO4 to TeO3. Absorption spectra revealed the high visible transparency of these samples and an increase of the optical band gap with GeO2 addition, in agreement with a decreasing polarizability of the glass network. Er3+ doped and Er3+/Yb3+ codoped samples were also studied with respect to their infrared emission properties and higher GeO2 contents lead to an increase in IR emission intensity at 1,5 mu m as well as longer radiative lifetimes. Finally, upconversion emission in the visible were also recorded and were shown to be strongly dependent of the composition. (C) 2016 Elsevier B.V. All rights reserved.